Prodorylaimus baikalensis sp. n. and Mononchus minutus sp. n. (Nematoda) from Lake Baikal, Russia - Naumova, Tatyana V.; Gagarin, Vladimir G. (Zootaxa, 2018)
Two new nematode species found in Lake Baikal (Russia) are described and illustrated. Prodorylaimus baikalensis sp. n. is morphologically close to P. irminii Vinciguerra & Orselli, 2011 and P. obesus Ahmad & Jarajpuri, 1982. From the first species it differs by the shorter and thinner body, longer tail, longer odontostyle and greater number of ventromedian supplements. From the second species it differs by the longer and more slender tail, shorter odontophore, longer female prerectum and greater number of ventromedian supplements in males. Mononchus minutus sp. n. is similar to M. niddensis Skwarra, 1921 and M. agilis Gagarin & Mataphonov, 2004. The new species differs from M. niddensis by the shorter body, more slender tail, longer buccal cavity, longer spicules and smaller number of ventromedian supplements in males. From M. agilis it differs by the shorter and thinner body, shorter tail, longer spicules and smaller number of ventromedian supplements in males.